Cost of agricultural business equity capital: A theoretical and empirical study for Poland - Justyna Franc-Dąbrowska; Magdalena Mądra-Sawicka; Joanna Bereżnicka (Economies, 2018)
This paper proposes a methodology for calculating the cost of equity for unlisted agricultural companies in Poland. An analysis of a fixed effects panel model was conducted on a sample of 79 agricultural enterprises from the Farm Accountancy Data Network (FADN) field of observation in 2012-2015. The empirical model includes a value of land, agricultural area, depreciation, sale earnings, and payables. The study confirmed that in the valuation of the cost of equity capital in agricultural enterprises, factors that are specific to this sector must be taken into account. As the basic source of production is agricultural land, it must be taken into consideration while estimating the cost of equity capital. This factor was included in the theoretical model.
Keywords: G31; Q12; 330; cost of equity capital; agricultural business; Farm Accountancy Data Network (FADN); farmland value factor; risk of the depreciation of farmland